Documentário-ensaio: a produção de um discurso audiovisual em documentários brasileiros contemporâneos - Carvalho, Ananda (2008)
The present research castes some elements to map the specificities of the essay-documentary. The Brazilian documentary s production has grown progressively in the last two decades, however a part of it no longer limits itself to a reproduction of the reality, characteristic traditionally associated to that type of production. In order to study those new works, this Master s Dissertation broadens the documentary concept to essay-documentary , acknowledging it as a subjective reflection about the world. That perspective is an unfolding of the concept of film essay, from Arlindo Machado, which reaches the productions that overpass the limits of the documentary and do not ties to the dichotomy between fiction and non-fiction or to the concern with a truth as a mirror of the reality. About the essay, it is adopted the concept of Theodor Adorno, which refers to the construction of an experimental and not totalitarian speech. To think the documentary as audiovisual, it gets back to Jean-Claude Bernadet, which contrasted that feature in the Brazilians contemporary documental productions. It is chosen to study the construction of that writing through the montage or the conceptual editing. To understand the montage, it returns to the concepts proposed by Serguei Eisenstein and Dziga Vertov, and followed by the video language according to Philippe Dubois and Arlindo Machado, until it arrives to the concept of metamedium and of montage as a spatial composition, proposed by Lev Manovich. At last, in order to consolidate the essay-documentary, it is chosen works which allowed establishing a dialogue between the theoretical perspectives approached. In this sense, it is presented an analysis divided in three sub themes: the montage of the visual speech, the montage of the sonorous speech and the symbolic montage. Each one of those sub themes is approached from a key-documentary, with the aim of realizing a reflection more deepen: Andarilho (Cao Guimarães), Sonoroscópio SP: polifonia da imigração (Kiko Goifman e Rachel Monteiro) and Nós que aqui estamos por vós esperamos (Marcelo Masagão). The selection tried to stand out production which was not restricted to the verbal as a speech composition strategy, but which adopted both images and soundtracks to build a symbolic documental writing